Growing up Asian in Australia - Pung, Alice (Black Inc., 2008)
"This is an anthology of writing about what it is really like to grow up Asian-Australian. Including contributions from established writers, public figures and exciting new talents, this diverse and unpredictable collection throws out the cliches and takes readers behind the stereotypes" -- Provided by publisher.